Olfactomedin-3 Enhances Seizure Activity by Interacting With AMPA Receptors in Epilepsy Models - Tang, Shirong; Wang, Tiancheng; Zhang, Xiaogang; Guo, Yi; Xu, Ping; Zeng, Junwei; Luo, Zhong; Li, Dongxu; Zheng, Yongsu; Luo, Yuemei; Yu, Changyin; Xu, Zucai (Frontiers in Cell and Developmental Biology, 2020)
Background: OLFM3 (olfactomedin-3) is a member of the olfactomedin domain family, which has been found to stimulate the formation and adhesion of tight cell connections and to regulate cytoskeleton formation and cell migration. Differences in the gene coding for OLFM3 have been found between patients with epilepsy and controls. However, the exact role of OLFM3 in epilepsy has not been thoroughly investigated. Methods: Biochemical methods were used to assess OLFM3 expression and localization in the cortex of patients with temporal lobe epilepsy and in the hippocampus and cortex of epileptic mice. Electrophysiological recordings were used to measure the role of OLFM3 in regulating hippocampal excitability in a model of magnesium-free-induced seizure in vitro. Behavioural experiments were performed in a pentylenetetrazol (PTZ)-induced seizure model, and electroencephalograms (EEGs) were recorded in the chronic phase of the kainic acid (KA)-induced epilepsy model in vivo. OLFM3 and its interaction with AMPAR (α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor) subunits were analysed by co-immunoprecipitation. Results: The expression of OLFM3 was increased in the cortex of patients with temporal lobe epilepsy and in the hippocampus and cortex of epileptic mice compared with controls. Interestingly, lentivirus-mediated overexpression of OLFM3 in the hippocampus increased the susceptibility of mice to PTZ-induced seizures, and OLFM3 knockdown had the opposite effect. OLFM3 affected AMPAR currents in a brain-slice model of epileptiform activity induced by Mg2+-free medium. We found that OLFM3 co-immunoprecipitated with GluA1 and GluA2. Furthermore, downregulation or overexpression of OLFM3 in the hippocampus affected the membrane expression of GluA1 and GluA2 in epileptic mice. Conclusion: These findings reveal that OLFM3 may enhance seizure activity by interacting with GluA1 and GluA2, potentially indicating a molecular mechanism for new therapeutic strategies.